2016
DOI: 10.4269/ajtmh.15-0663
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Increase in Scrub Typhus Incidence in Mainland China, 2006–2014

Abstract: Abstract. Scrub typhus is a vector-borne disease, which has recently reemerged in China. In this study, we describe the distribution and incidence of scrub typhus cases in China from 2006 to 2014 and quantify differences in scrub typhus cases with respect to sex, age, and occupation. The results of our study indicate that the annual incidence of scrub typhus has increased during the study period. The number of cases peaked in 2014, which was 12.8 times greater than the number of cases reported in 2006. Most (7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
48
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(54 citation statements)
references
References 11 publications
(12 reference statements)
6
48
0
Order By: Relevance
“…The results showed that the incidence of scrub typhus among females was higher than that observed in males, which is consistent with previous studies[17, 18]. Two factors may contribute the result.…”
Section: Discussionsupporting
confidence: 92%
“…The results showed that the incidence of scrub typhus among females was higher than that observed in males, which is consistent with previous studies[17, 18]. Two factors may contribute the result.…”
Section: Discussionsupporting
confidence: 92%
“…Wu et al have described a rise in the incidence of scrub typhus in Mainland China between 2006 and 2014 with a 12.8 times increase. 56 On top of seasonal peaks, the authors postulated that the increase of popularity in ecotourism have exposed more people to vector habitats. 56 Clinical manifestations typically include myalgia, high fevers, headaches, as well as a rash and eschar at the chigger bite.…”
Section: Scrub Typhusmentioning
confidence: 99%
“…56 On top of seasonal peaks, the authors postulated that the increase of popularity in ecotourism have exposed more people to vector habitats. 56 Clinical manifestations typically include myalgia, high fevers, headaches, as well as a rash and eschar at the chigger bite. Scrub typhus is usually self-limiting over 2-3 weeks but is sometimes associated with severe illness and multiorgan failure leading to death, although this is rare.…”
Section: Scrub Typhusmentioning
confidence: 99%
“…Within each province, the population is served by a central provincial hospital, district hospitals and primary care or health promoting units located in every sub-district. There has been an increase in notified cases reported from other countries with established passive notification systems such as South Korea, China and Bhutan, while results from Japan and more recently Taiwan suggest the disease incidence has stabilised [15,[32][33][34][35][36][37].…”
mentioning
confidence: 99%